Anterior abdominal wall abscess caused by Streptococcus pneumoniae in a patient with self-inflicted stab injury: An unusual presentation - Shailesh Kumar; Sivaraman Umadevi; Joshy Maducolil Easow; Noyal Mariya Joseph; Sreenivasan Srirangaraj; Kandha Kumari; Selvaraj Stephen (Journal of Infection in Developing Countries)
Streptococcus pneumoniae is a major cause of community-acquired pneumonia, otitis media, paranasal sinusitis, bacteremia and meningitis, as well as osteomyelitis and occasionally peritonitis. We report the case of a 25-year-old female who had stabbed herself with a kitchen knife above the umbilicus 10 days prior to admission. Subsequently, she developed an anterior abdominal wall abscess caused by S. pneumoniae. This case is unusual as the focus was distant from the respiratory tract, the usual primary site of infection caused by this organism. Furthermore, the case assumes significance because it occurred in the absence of any typical risk factors for S. pneumoniae.